Analisis Kecacatan pada Produksi Syringe Barrel Menggunakan Basic Quality Tools - Renggananta, Adhista Triasa; Fazrin, Reza Aulia; Maula, Putri Amanatul; Safira, Raudita Nadya; Wiguna, I Gusti Gede Arya; , Adithia Pamungkas; Ferdiyansyah (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Enhancing the quality of medical products such as syringe barrels requires a systematic quality control approach to ensure safety and process consistency. This study aims to analyze defects occurring in the syringe barrel manufacturing process using basic quality tools. Defect data were collected and examined using check sheets, histograms, Pareto charts, and control charts. The results of the Pareto analysis indicate that four types of defects: contamination, partial printing loss, bruising, and scratches, account for the majority of total defects and therefore require further investigation. These four defect categories were subsequently analyzed using a p-control chart to evaluate process stability. The control chart results show that all data points fall within the control limits (UCL and LCL), indicating that the process remains statistically stable and under control. These findings suggest that although defects are present, the production process can still be considered controlled, and improvement efforts should therefore focus on reducing variation arising from common causes.